2010
DOI: 10.1097/sle.0b013e3181cdebf4
|View full text |Cite
|
Sign up to set email alerts
|

Complications of Metallic Stent Placement in Malignant Esophageal Stricture and Their Management

Abstract: The complication rate of self-expandable metallic stent placement is high in inoperable esophageal cancer patients. Although some of these complications are life threatening, many of them can be managed successfully with endoscopic reintervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
23
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 43 publications
1
23
0
2
Order By: Relevance
“…However, if symptomatic, the stent should be removed by endoscopy or surgical incision. [3] In our study, while an incomplete migration was observed in 3.7% of the patients, the stent displaced into the stomach in 2.9% of cases. While the stent was pulled back to its normal location by endoscope in all patients with incomplete migration, the stent was removed by employing gastrotomy after a mini-laparotomy in five of the eight patients with total migration to stomach.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…However, if symptomatic, the stent should be removed by endoscopy or surgical incision. [3] In our study, while an incomplete migration was observed in 3.7% of the patients, the stent displaced into the stomach in 2.9% of cases. While the stent was pulled back to its normal location by endoscope in all patients with incomplete migration, the stent was removed by employing gastrotomy after a mini-laparotomy in five of the eight patients with total migration to stomach.…”
Section: Discussionmentioning
confidence: 88%
“…[1,3,8,18] In our study, a re-intervention (new stent placement, removal of the stent, stent dilation, or removal of food residues) became necessary in 72 (26.9%) patients. Considering that the mortality rate was low (1.5%) and the mean survival rate was approximately six months in our study, we may conclude that esophageal stent provides significant palliation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5 Furthermore, it is recommended that radiation therapy should precede stent placement for patients with locally advanced esophageal cancer with severe dysphagia, because the consequences of radiation therapy after stent placement often lead to complications such as bleeding, stent migration, and perforation of the esophagus. 6 However, previous radiotherapy and chemotherapy is often a contraindication for stent placement in patients with malignant tracheoesophageal/bronchoesophageal fistulas.…”
Section: Discussionmentioning
confidence: 99%